A grounded theory study of family caregivers' responses to the sexuality of young adults with intellectual disabilities - Kahonde, Callista Kanganwiro (Department of Health and Rehabilitation Sciences, 2017)
Globally, people with intellectual disabilities are not afforded equal opportunities to express and enjoy their sexuality on par with their peers. Although most of them remain under the lifetime custody of family caregivers for care and support, a knowledge gap exists in understanding the role of the family caregivers in the sexuality issues of people with intellectual disabilities, especially in developing countries like South Africa. The present study is the first of its kind that employed an exploratory, theory generating methodology, the constructivist grounded theory methodology, to seek understanding of how family caregivers in the Western Cape Province of South Africa respond to sexuality of young adults with intellectual disabilities. Data were gathered through in-depth and focus group interviews with 25 family caregivers and further confirmatory interviews with nine service providers of young adults with intellectual disabilities. The study generated a substantive grounded theory, the Theory of Contained Sexuality, to explain the responses of family caregivers to the sexuality of young adults with intellectual disabilities. The study found that the family caregivers' thoughts, emotions, actions and behaviour towards the sexuality of the young adults with intellectual disabilities are influenced by what the family caregivers see as implications of the young adults' sexual expression and behaviour on both of them. The family caregivers do not completely suppress or restrain the sexuality of the young adults with intellectual disabilities but they support with 'containment', that is they try to confine the sexuality within boundaries that they can control and manage within their lifelong caring role. Ultimately, what the findings of this study point towards is the impact of lifelong family care on realisation of sexual rights by people with intellectual disabilities. Hence, the study concluded that, without the appropriate forms of support and probably alternative forms of care, the human rights framework as embodied within the United Nations Convention on the Rights of Persons with Disabilities and local policies informed by it is insufficient as a tool for sexual emancipation of people with intellectual disabilities. Therefore, a relational moral theory - the ethics of care - is proposed as appropriate to complement the human rights framework in both research and practice around sexuality of people with intellectual disabilities living under family care. The study also highlights the imperative for further studies that investigate the impact of lifelong family care on other aspects of the lives of people with intellectual disabilities and promote theorisation of lifelong care within such studies.